2002
DOI: 10.1074/jbc.m200544200
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and Postprandial Overproduction of Intestinally Derived Lipoproteins in an Animal Model of Insulin Resistance

Abstract: Insulin-resistant states are characterized by hypertriglyceridemia, predominantly because of overproduction of hepatic very low density lipoprotein particles. The additional contribution of intestinal lipoprotein overproduction to the dyslipidemia of insulin-resistant states has not been previously appreciated. Here, we have investigated intestinal lipoprotein production in a fructose-fed hamster model of insulin resistance previously documented to have whole body and hepatic insulin resistance, and hepatic ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
79
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(90 citation statements)
references
References 57 publications
6
79
2
Order By: Relevance
“…23 The consequences of the insulin signaling defect at the level of the enterocyte are an increase in de novo lipogenesis and chylomicron assembly and secretion. 23,29,30 We also confirmed the results of several studies in animal models of insulin resistance 22,31,32 in type 2 diabetic 20 and obese, insulin-resistant human subjects, 21 showing that the acute inhibitory effect of insulin on hepatic TRL-apoB-100 production is blunted.The kinetic parameters of our study are different (lower PS and PR and higher FCR) with regard to those of the only kinetic study on TRL-apoB-48 metabolism in type 2 diabetic subjects versus controls, 8 but several differences between the 2 studies may explain these discrepancies. The diabetic population in that study was more insulin resistant (mean HOMA-IR: 5.6 versus 4.4) and was frankly more hypertriglyceridemic (mean fasting plasma TG levels: 4.6 versus 2.0 mmol/L) than our diabetic population.…”
supporting
confidence: 75%
“…23 The consequences of the insulin signaling defect at the level of the enterocyte are an increase in de novo lipogenesis and chylomicron assembly and secretion. 23,29,30 We also confirmed the results of several studies in animal models of insulin resistance 22,31,32 in type 2 diabetic 20 and obese, insulin-resistant human subjects, 21 showing that the acute inhibitory effect of insulin on hepatic TRL-apoB-100 production is blunted.The kinetic parameters of our study are different (lower PS and PR and higher FCR) with regard to those of the only kinetic study on TRL-apoB-48 metabolism in type 2 diabetic subjects versus controls, 8 but several differences between the 2 studies may explain these discrepancies. The diabetic population in that study was more insulin resistant (mean HOMA-IR: 5.6 versus 4.4) and was frankly more hypertriglyceridemic (mean fasting plasma TG levels: 4.6 versus 2.0 mmol/L) than our diabetic population.…”
supporting
confidence: 75%
“…This enhanced production of FFAs might induce the de novo lipogenesis of TG, resulting in the increased synthesis of intestine-derived lipoproteins. Haidari et al (28) showed that the de novo synthesis of FA and apoB-48-containing lipoproteins in the intestine of fructose-fed hamsters was increased. Even though this result was observed in an animal model of insulin resistance model, it was suggested that the endogenous production of fatty acids might influence the apoB-48-containing lipoprotein secretion in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of the insulin resistant state in fructose-fed hamsters is associated with overproduction of apo B 48 containing particles [91]. There is also evidence that intestinal MTP is increased in diabetic animals and this could enhance the formation of apo B 48 containing particles [86,91]. Further studies are needed to delineate the exact contribution of intestinal overproduction of apo B 48 lipoproteins in diabetes to the postprandial lipemia in humans.…”
Section: Fat Intolerance In Type 2 Diabetesmentioning
confidence: 99%